Digit Ratio (2D:4D) and Physical Performance in Female Olympic Athletes - Eklund, Emma; Ekström, Lena; Thörngren, John-Olof; Ericsson, Magnus; Berglund, Bo; Hirschberg, Angelica Lindén (Frontiers in Endocrinology, 2020)
Background: The second to fourth digit ratio (2D:4D ratio) is suggested to be a negative correlate of prenatal testosterone. Little is known about the role of the 2D:4D ratio in relation to serum and urinary androgens for physical performance in female athletes. We aimed to compare the 2D:4D ratio in female Olympic athletes with sedentary controls, and to investigate the 2D:4D ratio in relation to serum and urinary androgens and physical performance in the athletes. Methods: This cross-sectional study included 104 Swedish female Olympic athletes participating in power, endurance and technical sports and 117 sedentary controls. The 2D:4D ratio was calculated using direct digit measurements. Serum androgens and urinary androgen metabolites were analyzed by liquid chromatography-tandem mass spectrometry. The athletes performed standardized physical performance tests and body composition was established by dual-energy X-ray absorptiometry. Results: The 2D:4D ratio was significantly lower in the athletes compared with controls although serum testosterone levels were comparable between groups and within normal reference values. The 2D:4D ratio correlated negatively with urinary levels of testosterone glucuronide and 5α- and 5βAdiol-17G, whereas there were no correlations to serum androgen levels. Furthermore, the 2D:4D ratio correlated negatively with strength tests and positively with 3000-meter running in the athletes. Conclusion: Female Olympic athletes had a lower 2D:4D ratio, possibly reflecting a higher prenatal androgen exposure, than sedentary controls. Furthermore, the 2D:4D ratio was related to urinary levels of androgen metabolites and physical performance in the athletes but not to serum androgen levels. It is suggested that the 2D:4D ratio could reflect androgen metabolism and may be of importance for sporting success in female athletes.